Modern Approaches to English Language Teaching and Learning: Addressing the Need for Language Capability in the 21st Century World (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Increasing global economies, a heightened need for matching the international standards and changing demographics in the world have increased attention to our country’s lack of language capability in terms of transacting in foreign languages, especially the English language. Every call to action to prepare our students for the 21st Century includes offering them the opportunity to learn English so as to increase their knowledge of other cultures. The hall mark of success in the 21stcentury world certainly amounts to two key factors one is digital literacy and the other knowledge of English language.